English club ISSC Demovid competition (October - November 2021) / Muhammad Aiman Abdul Halim, Noor Azli Affendy Lee and Nur Ilianis Adnan - Abdul Halim, Muhammad Aiman; Affendy Lee, Noor Azli; Adnan, Nur Ilianis (Academy of Language Studies, 2022)
The English Language Club of UiTM Cawangan Pulau Pinang had organised two competitions: Idiom-Based Short Story Competition and Demonstrative Video Competition. Both competitions were held from 11 October until 28 November 2021. The main objectives are to encourage students to write and speak in the English language, as well as improve vocabulary. There are two categories for each competition: school students and university students. They can participate for free, simply by posting their works on Instagram and including certain hashtags. One of the reasons why Instagram was chosen as the competition platform is due to its popularity among teenagers and young adults. To add more excitement, winners are awarded monetary prizes amounting to RM100 for first place, RM75 for second place and RM50 for third place